2007
DOI: 10.1080/13803390601147686
|View full text |Cite
|
Sign up to set email alerts
|

A longitudinal analysis of neurocognitive function in unipolar depression

Abstract: Neurocognitive function is reduced in major depression, but uncertainties remain about if and to what extent improvement in neurocognitive function follows remission of depressive symptoms. A total of 30 patients with Diagnostic and Statistical Manual of Mental Disorders-Fourth Edition (DSM-IV) diagnosis of unipolar major depressive disorder (MDD) at baseline were tested neuropsychologically again, after a mean test-retest interval of 2 years. At retest, patients were partly or completely recovered from depres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
63
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(67 citation statements)
references
References 45 publications
3
63
0
1
Order By: Relevance
“…However, in this study, HAM-D7 scores were found to be more important for predicting symptomatic improvement than DST scores used to assess verbal WM, a finding well in line with that reported by Biringer et al (2007), who showed that neurocognitive function at baseline did not predict amelioration of depressive symptoms over time in young adults. The present results, however, suggest verbal WM to be more important for predicting functional out- comes than depressive symptoms.…”
Section: Discussionsupporting
confidence: 79%
“…However, in this study, HAM-D7 scores were found to be more important for predicting symptomatic improvement than DST scores used to assess verbal WM, a finding well in line with that reported by Biringer et al (2007), who showed that neurocognitive function at baseline did not predict amelioration of depressive symptoms over time in young adults. The present results, however, suggest verbal WM to be more important for predicting functional out- comes than depressive symptoms.…”
Section: Discussionsupporting
confidence: 79%
“…This sparing concerns not only processing speed, working memory and overall executive functioning, but also episodic memory performances thought to be particularly vulnerable in the long-term evolution of EOD [5]. As already suggested in younger adults [39], this vulnerability may be related to the acute stages of the disease and be reversible. Two previous reports also challenged the deleterious effect of chronic depression in cognition [13,14].…”
Section: Discussionmentioning
confidence: 93%
“…25 The BDI measures severity of depression and classifies results as minimal (score, 0-11), mild (score, [12][13][14][15][16][17][18][19], moderate (score, 20-35), or severe (score, 36-63).…”
Section: Instruments and Outcome Measuresmentioning
confidence: 99%
“…17 For instance, neurocognitive function at baseline was not predictive of symptom improvement in depression. 18 Although some speculate that cognition may mediate change in psychotherapy, 3 a definite statement that neurocognitive processes serve as mediators of therapeutic change would be premature, because researchers are only beginning to study the relationship between neurocognition and treatment outcome. For this reason, using neurocognitive variables as possible predictors is relevant for intervention research.…”
Section: Introductionmentioning
confidence: 99%